Design Tools to Audit Electricity - Supriyadi, Kuat; Fakhlur Dewantoro; Ipin Prasojo; Septi Aprilia; Elsa Sari Hayunah Nurdiniyah (Indonesian Journal of Advanced Research, 2024)
Until now, energy has had a very important role in the life of human civilization. One of the problems that arise in the use of energy is that there is still a lot of use of fossil energy, even though this energy is very limited on Earth. Therefore, the need for efficiency in energy use in all areas of life, including in government, private, and community institutions. But doing so, of course, requires a measuring instrument that is practically inexpensive and highly efficient. The application system is the right answer to solving this problem, so the authors conduct research by making measuring instruments that can record digitally in memory and with the Internet of Things system so that analysis will be faster and more accurate, and by not using cables as data distribution.